Prospective evaluation of where reperfusion ventricular arrhythmia "bursts" fit into optimal reperfusion in STEMI. (15th September 2015) - van der Weg, Kirian; Kuijt, Wichert J.; Tijssen, Jan G.P.; Bekkers, Sebastiaan C.A.M.; Haeck, Joost D.E.; Green, Cynthia L.; Lemmert, Miguel E.; de Winter, Robbert J.; Gorgels, Anton P.M.; Krucoff, Mitchell W.
Abstract: Background: Early reperfusion of ischemic myocytes is essential for optimal salvage in acute myocardial infarction. VA (ventricular arrhythmia) bursts after recanalization of the culprit vessel have been found to be related to larger infarct size (IS), using SPECT. Objective: The hypothesis was tested that this finding could be confirmed in an independent cohort using a more accurate technique, i.e. delayed-enhancement cardiovascular magnetic resonance imaging (DE-CMR). Methods: All 196 patients from the PREPARE and MAST studies who had 24-hour, continuous, 12-lead Holter, started before primary percutaneous coronary intervention resulting in brisk TIMI (thrombolysis in myocardial infarction) 3 flow and stable ST-recovery were included. VA bursts were identified against subject-specific background VA rates using a previously published statistical outlier method. IS was assessed using DE-CMR. Angiography, Holter and DE-CMR results were assessed in core laboratories, blinded to all other data. Results: VA bursts were present in 154/196 (79%) of patients. Baseline characteristics between the groups with and without bursts were similar. VA burst was associated with significantly larger infarct size in the population as a whole (median 11.3% vs 5.3%; p = 0.001) and also when divided in non-anterior (median 9.9% vs 4.9%; p = 0.003) and anterior myocardial infarction (median 21.4% vs 12.0%; p = 0.48), the latter not reaching statistical significance due to the small subset of patients. Conclusion: Beyond the classical markers of "optimal" reperfusion such as TIMI 3 flow and stable ST-segment recovery, VA bursts occurring during the reperfusion phase are an early electrobiomarker of larger IS. Clinical trial registration: PREPARE: ISRCTN71104460http://www.controlled-trials.com/ISRCTN71104460 .